Algebra

Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work.

sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7)
sqrt(7*x)-7*sqrt(7*7)
sqrt(7x)-7*sqrt(7^2)
x*sqrt 7x-49*x

^^^ would this be my final answer?

  1. 👍
  2. 👎
  3. 👁
  1. Assuming you meant:

    √7 x(√x - 7√7)
    = x√(7x) - 49x

    brackets are important here

    e.g √(7x) vs √7x , the last one is (√7)x

    1. 👍
    2. 👎

Respond to this Question

First Name

Your Response

Similar Questions

  1. algebra

    Simplify: 2 sqrt (3) + 6 sqrt(2) - 4 sqrt(3) + sqrt (2) a) 8 sqrt(2) - 3 sqrt(3) b) 6 sqrt(2) - 8 sqrt(3) c) 5 sqrt(6) d) 7 sqrt(2) - 2 sqrt(3) the answer i picked was d

  2. algebra

    Simplify: sqrt (21) (sqrt(7) + sqrt(3)) a) 7 sqrt (3) + 3 sqrt(7) b) 7 sqrt(3) + sqrt (3) c) sqrt (210) d) sqrt (147) + sqrt (63)''. a

  3. math;)

    Find the unit vector in the direction of u=(-3,2). Write your answer as a linear combination of the standard unit vectors i and j. a. u=-3[sqrt(13)/13]i+2[sqrt(13)/13]j b. u=-3[sqrt(5)/5]i+2[sqrt(5)/5]j c.

  4. algebra

    what is the simplified form of 3 sqrt (5c) x sqrt (15c^3) choices are a. 15c^2 sqrt (3) b.6c^2 sqrt (5) c. 5c^2 sqrt(3) d. 12c^4 sqrt(5) please help i don't understand how to do the question i would really appreciate it

  1. is this correct?- math

    find the domain of the real valued function; f(x) = sqrt(5 - (sqrtx)) my solution: 5 - (sqrt x) >=0 -(sqrt x) >= -5 (sqrt x)

  2. math

    Simplify each radical expression. Leave in radical form. Show your work. 6.sqrt 75 + sqrt 3 7. sqrt7(sqrt 14 + sqrt3 ) please.

  3. algebra

    simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 +

  4. algebra

    Simplify -11 sqrt 112. -44 sqrt 7******** -176 sqrt 7 -27 sqrt 7 4 sqrt 7 Is this right? and I need to show my work, idk the steps

  1. Calculus

    Evaluate the indefinite integral: 8x-x^2. I got this but I the homework system says its wrong:sqrt((-x-8)x)/(2*sqrt(x-8)*sqrt(x))*(((sqrt(x-8)*(x-4)*sqrt(x))-32*log(sqrt(x-8)+sqrt(x))

  2. algebra

    am I right? 1. Simplify radical expression sqrt 50 5 sqrt ^2*** 2 sqrt ^5 5 sqrt ^10 5 2. Simplify the radical expression sqrt 56x^2 28x 2x sqrt 14*** 2x sqrt 7 sqrt 14x2 3. Simplify the radical expression. sqrt 490y^5w^6 2 sqrt

  3. Algebra

    Which of these expressions is in simplified form? A. a ^3 sqrt 4 - b ^3 sqrt 2 / 2 B. sqrt 1/2x + sqrt 1/2z C. x^2 - 3x sqrt y / sqrt 3 D. sqrt 125x - x^2

  4. Calculus - Second Order Differential Equations

    Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2

You can view more similar questions or ask a new question.